Effect of Rotation and Suspended Particles on the Stability of an Incompressible Walters’ (Model B′) Fluid Heated from Below Under a Variable Gravity Field in a Porous Medium - RANA, G. C.; KUMAR, SANJEEV (Engineering Transactions, 2012)
The effect of rotation and suspended particles on the stability of an incompressible Wal- ters’ (model B′) fluid heated from below under a variable gravity field in a porous medium is considered. By applying a normal mode analysis method, the dispersion relation has been derived and solved numerically. It is observed that the rotation, gravity field, suspended par- ticles, and viscoelasticity introduce oscillatory modes. For stationary convection, the rotation has a stabilizing effect and suspended particles are found to have a destabilizing effect on the system, whereas the medium permeability has a stabilizing or destabilizing effect on the system under certain conditions. The effect of rotation, suspended particles, and medium permeability has also been shown graphically.